Comparative Analysis of Integration Policies in Switzerland, Germany, and Türkiye: Is Türkiye a Country of Immigration? - Ertuğrul Gökçekuyu (İnsan & Toplum)
This article performs a comparative analysis to evaluate the importance of immigration policies by studying the experiences of Swiss, German, and Turkish immigration policies. As a relatively recent immigration destination, Türkiye faces challenges and the resultant struggles between regulating immigrants and public sentiments. The central objective of this exploration of past political dynamics aims to demonstrate the paths to be learned regarding policymaking for Türkiye, where Turkish experiences are not only new but are also marked by new legislation such as the 2013 Law on Foreigners and International Protection (YUKK). While YUKK regulates immigration, it does not offer integration policies. This analysis situates Türkiye’s immigration experiences in a broader context by looking at the successes and shortcomings of Swiss and German immigration policies. More importantly the study presents crucial insights for Türkiye’s policy framework, which views immigration as a temporary phenomenon. Nevertheless, the inception of the Syrian conflict in 2011 revealed Turkish society to have enacted significant public scrutiny regarding immigration. Turkish immigration experiences at this point in time overlook integrationist policies comparable to the past Swiss and German assumption that someday immigrants will return home. The analysis based on insulation theory shows that starting integration policies is the first step to Turks acknowledging their own country as an immigration country. The central question of the analysis is how Türkiye’s immigration policies have evolved to address long-term integration challenges by drawing on comparative lessons from Swiss and German immigration experiences. One important finding from the analysis is that the Turkish government relies on short-term regulative legislation similar to the historical Swiss and German immigration policies. This approach renders Türkiye unable to accept itself as a permanent immigration country, thereby underlining the importance of adopting comprehensive social integration policies.